IMPLEMENTATION OF INDEPENDENT LEARNING CURRICULUM AS A 21st CENTURY LEARNING MODEL IN HIGHER EDUCATION - Dwi Lutfi Nur Anisa (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to describe the implementation of independent learning curriculum in higher institutions. The independent learning curriculum is newly implemented to respond to the needs of industry 4.0. The Independent learning curriculum is implemented by applying student-centered learning. Students are free to choose the field of science they are interested in even though they are cross-departmental. The method used is a systematic review using the prism method by analyzing research manuscripts. The steps in a systematic review using the Prisma model include; defining eligibility criteria, defining sources of information, selecting literature, collecting data, and selecting data items. Based on the results of the review, it was found that the independent learning curriculum can answer the challenges of industry 4.0. The implementation of the independent learning curriculum is carried out through three aspects, namely, 1) collaboration of the campus curriculum with the independent learning curriculum, 2) the availability of learning facilities, and 3) the development of learning tools. The fulfillment of these three aspects will positively impact the multidisciplinary competence of students.